Treatment with the SGLT2 inhibitor luseogliflozin improves nonalcoholic steatohepatitis in a rodent model with diabetes mellitus. Issue 1 (December 2015) - Qiang, Shirong; Nakatsu, Yusuke; Seno, Yasuyuki; Fujishiro, Midori; Sakoda, Hideyuki; Kushiyama, Akifumi; Mori, Keiichi; Matsunaga, Yasuka; Yamamotoya, Takeshi; Kamata, Hideaki; Asano, Tomoichiro
Abstract Background Insulin resistance with elevated glucose is a risk factor for non-alcoholic steatohepatitis (NASH). We investigated the effects of the sodium glucose cotransporter 2 (SGLT2) inhibitor luseogliflozin on NASH development using a rodent model. Methods Mice were treated with both nicotinamide and streptozotocin (NA/STZ) to reduce insulin secretory capacity, and then fed a high fat diet containing trans fatty acids (HFDT) for 8 weeks. The NA/STZ HFDT-fed mice were divided into two groups, either treated with luseogliflozin or untreated, during this period. The glucose elevations in the NA/STZ-treated and HFDT-fed mice were significantly improved by luseogliflozin administration. While HFDT feeding induced NASH development as shown by liver weight gain with lipid accumulation and increased serum alanine aminotransferase, these changes were all attenuated in the group treated with luseogliflozin. In addition, fibrotic change and increases in collagen deposition with upregulations of collagen1 and smooth muscle actin and inflammatory cytokine expressions observed in the HFDT-fed mouse livers were also normalized by luseogliflozin administration. Conclusions Taken together, these results obtained in mice demonstrate the favorable effects of administering SGLT2 inhibitors, for the treatment of NASH associated with diabetes mellitus. We anticipate that these agents would be applicable to humans.